Nonlinear Polarization Evolution Mode-Locked YDFL Based on All-PM Fiber Cavity - Zhichao Wu; Qian Wei; Pan Huang; Songnian Fu; Deming Liu; Tianye Huang (IEEE Photonics Journal, 2020)
Polarization-maintaining (PM) all-fiber cavity is always essential to realize stable ultrafast-pulse generation. With the help of five sections of PM fibers with independently specific splicing angles, we successfully obtain a femtosecond pulse output from a PM Ytterbium-doped fiber laser (YDFL) mode-locked by the nonlinear polarization evolution (NPE) technique. Using a hybrid component, the PM all-fiber cavity can be greatly simplified. Ultrafast-pulses with 24.5-MHz repetition rate, 20-nm spectral bandwidth, and 260-fs pulse duration after external compression can be steadily generated. In comparison with the non-PM fiber cavity, the proposed YDFL has excellent long-term environmental stability, making it ideal for various practical applications.